Análise da importância de controladores digitais na medição da temperatura do enrolamento em transformadores a óleo - Lima, Gustavo Sales de (2015)
This work aims to present an analysis of temperature rise test on transformers associated with the definition of control parameters in the measurement and monitoring of temperature, oil transformers, focusing on the evolution of this control with the use of digital controllers on the market, their functionality and interface with the operator and optimization of temperature monitoring of transformers. The temperature being a variable of important diagnosis in the life of the transformer, but not taken into account by many buyers who contact the manufacturers at the time of purchase, posing as one of the technical requirements to obtain the real gradients involved in the set of parameters of the controllers today that existing monitoring, which can generate parameterized wrongly unreal values for efficient monitoring of this variable.